Using of costs based on activity that focused on performance in Reduce Costs and their reflection to improve competitive advantage: An applied research in wasitTextile and Knitting factory (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims mainly to the role of the statement style costs on the basis of activity based on performance (PFABC) to reduce production cost and improve the competitive advantage of economic units and industrial under the modern business environment dominated by a lot of developments and changes rapidly, which necessitates taking them and criticize them to ensure survival and continuity.  The research problem is the inability of traditional cost methods of providing useful information to the departments of units to take many administrative decisions, particularly decisions related to the product and calculating the costs of the quality of the sound and the availability of the need and the ability to replace methods capable cost of modern, such as the style of activity-based costing based on the performance PFABC  was reached for a set of conclusions including: still a textile factory and weaving Wasit depends on the traditional methods of costs when measuring its product costs, which would make him a minor to keep pace with developments and changes in the business environment, as a result of its limitations in determining the cost of its products properly, especially the industrial cost of indirect,  and reflection to determine the price.  The research also found a set of recommendations including: appropriate for the adoption of a textile factory and weaving Wasit methods of modern cost such as the cost method of management on the basis of activity based on performance (PFABC), which will have an important role in determining the cost of its products properly, especially the industrial non-cost directly, which  ultimately help in reducing the cost of its products